The hamburg lectures on maritime affairs 2011-2013 - Basedow, Jürgen; Magnus, Ulrich; Wolfrum, Rüdiger (Hamburg Studies on Maritime Affairs, International Max Planck Research School for Maritime Affairs at the University of Hamburg, 2015)
In 2007, the International Max Planck Research School for Maritime Affairs together with the International Tribunal for the Law of the Sea (ITLOS), both based in Hamburg, decided to establish an annual lecture series, the "Hamburg Lectures on Maritime Affairs" - giving distinguished scholars and practitioners the opportunity to present and discuss recent developments in this field. The present volume - the third in the series - collects the lectures held between 2011 and 2013 inter alia by Andrew Dickinson, Yvonne Marie Dutton, Bevan Marten, Andreas Maurer, Irini Papanicolopulu, Časlav Pejovic, Juan L. Pulido, Andrés Recalde Castells, Thomas J. Schoenbaum and Rüdiger Wolfrum.